1999
DOI: 10.1021/ja9725256
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition Abilities of a New Class of Water-Soluble Cyclophanes Capable of Encompassing a Neutral Cavity

Abstract: We developed a new class of water-soluble cyclophanes, pyrenophanes, capable of encompassing a neutral cavity, in which the hydrophobic area is constructed by aligning two flat polynuclear aromatic rings parallel at an appropriate space that could interpose just one layer of aromatic plane. The height, depth, and width of the cavity in an open conformation of the pyrenophane are 0.46, 0.95, and 1.31 nm, respectively, i.e., the area of this cavity is so large that even porphirin compounds might be incorporated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 18 publications
0
48
0
1
Order By: Relevance
“…205,206 In this case, preliminary studies with receptor 96a in 3:1 water:ethylene glycol revealed a change in the absorption spectrum upon the addition of a variety of guests, including nucleotide monophosphates AMP, UMP, GMP, and CMP. Among this latter class of substrates, a modest selectivity was observed for GMP ( K = 3.5 × 10 4 M -1 ).…”
Section: Major Phosphate-binding Functionalitiesmentioning
confidence: 92%
“…205,206 In this case, preliminary studies with receptor 96a in 3:1 water:ethylene glycol revealed a change in the absorption spectrum upon the addition of a variety of guests, including nucleotide monophosphates AMP, UMP, GMP, and CMP. Among this latter class of substrates, a modest selectivity was observed for GMP ( K = 3.5 × 10 4 M -1 ).…”
Section: Major Phosphate-binding Functionalitiesmentioning
confidence: 92%
“…As before, a system with a 90° twist would have been a useful addition to this study. The (1,6)pyrenophanes 37a-p, 37 several of which are watersoluble, are the largest and most elaborate pyrenophanes to have been reported to date. These systems were designed to have moderately rigid, side-chain-bearing frameworks that would encompass a neutral cavity and thereby resemble the hydrophobic areas of double helical DNA for the purpose of recognizing planar (aromatic) molecules in water.…”
Section: Scheme 5 Synthesis Of (13)pyrenophanes 24a-e and Reactions mentioning
confidence: 99%
“…[15][16][17] For example, poly( pyrenebutyric acid) has been used as a noncovalent stabilising unit for single-walled carbon nanotubes, preventing formation of bundles and enabling dispersion in solvents. 18 Pyrene has also found use in biological chemistry, especially in systems for binding nucleic acids, [19][20][21][22] and in the design of synthetic receptors for aromatic 23,24 and carbohydrate 25 substrates.…”
Section: Introductionmentioning
confidence: 99%